OPTIMIZATION OF CULTURE CONDITIONS FOR PENECILLIUM ISOLATED FROM SOIL TO ENHANCE AMYLASE PRODUCTION POTENTIAL (Pakistan Journal of Science, 2022)
The objective of present study was to evaluate amylase production potential of indigenous Penicillium sp. Amylase producing specie was isolated from soil of livestock farms using starch agar and confirmed as Penicillium by macroscopic and microscopic features. Non-toxigenecity was evaluated by thin layer chromatography. Optimization experiments were carried out by submerged fermentation using standardized inoculum (106 spores/mL) at pH 4.5, 6.0 and 7.5, temperature 22, 28 and 37°C and substrates wheat bran, maize and rice husk with varying concentrations of 1, 3 and 5 percent for seven days of incubation period. The amylase production was measured in terms of enzyme activity (IU) by dinitro salicylic acid (DNS) method. The optimum temperature and pH were 37°C and 6, respectively with mean enzyme activity of 17.52±.56 IU. Wheat bran proved to be the best substrate for amylase production by Penicillium sp. with 76.7149±3.53 IU at five percent concentration. A direct relation was found between substrate concentration and amylase enzyme activity (IU). It was concluded that Penicillium isolate was a potential candidate for amylase production on industrial level.
Keywords: Penicillium sp; amylase; wheat bran; maize and rice husk